2013
DOI: 10.1016/j.jaci.2012.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA profiles in bronchoalveolar lavage fluid exosomes in asthmatic patients

Abstract: Background Asthma is characterized by increased airway narrowing in response to nonspecific stimuli. The disorder is influenced by both environmental and genetic factors. Exosomes are nanosized vesicles of endosomal origin released from inflammatory and epithelial cells that have been implicated in asthma. In this study we characterized the microRNA (miRNA) content of exosomes in healthy control subjects and patients with mild intermittent asthma both at unprovoked baseline and in response to environmental cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
270
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(283 citation statements)
references
References 73 publications
4
270
4
5
Order By: Relevance
“…The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment. Several human and animal studies that assessed in vivo effects of respiratory exposures were not able to link changes in circulating EV to alterations in inflammatory markers (Emmerechts et al 2012a(Emmerechts et al , 2012bLevanen et al 2013;Mobarrez et al 2014). Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011).…”
Section: Conflicting Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment. Several human and animal studies that assessed in vivo effects of respiratory exposures were not able to link changes in circulating EV to alterations in inflammatory markers (Emmerechts et al 2012a(Emmerechts et al , 2012bLevanen et al 2013;Mobarrez et al 2014). Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011).…”
Section: Conflicting Datamentioning
confidence: 99%
“…Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011). In part, the failure to detect proinflammatory changes in EV in response to respiratory toxicants in vivo may be due to (1) use of relatively mild and acute exposures (Levanen et al 2013;Mobarrez et al 2014) or (2) the fact that current methods are not sensitive enough to detect subtle changes in EV and inflammatory mediators in study populations without clinical disease.…”
Section: Conflicting Datamentioning
confidence: 99%
“…There are at least three ways that miRNAs are protected from RNases. First, miRNAs can be contained within membrane-bound vesicles termed "exosomes" (40). Second, miRNAs can be bound by proteins such as Argonaute (41).…”
Section: Airway Epithelial Micrornas As Endotypic Markersmentioning
confidence: 99%
“…The variability in treatment response is based on large asthma clinical heterogeneity, and understanding the pattern of airway inflammation and molecular factors regulating those processes could be helpful in defining asthma endotypes and understanding why therapy is not effective in all patients 6 . MicroRNAs (miRNAs), 19-25 nucleotides long non-coding small RNAs involved in regulation of gene expression through a process known as RNA interference 729 , may play a role in orchestrating the phenotypic programming of immune and airway epithelial cells to enhance the production of cytokines and other mediators that result in the inflammation that characterizes asthma 3,4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Therefore, miRNAs may contribute to asthma pathology.…”
mentioning
confidence: 99%